Urban adults' perceptions of factors influencing asthma control. (February 2015) - George, Maureen; Keddem, Shimrit; Barg, Frances K.; Green, Sarah; Glanz, Karen
Abstract Objective: To identify urban adults' perceptions of facilitators and barriers to asthma control, including the role of self-care, medications, environmental trigger remediation, and primary care. Methods: Semi-structured open-ended qualitative interviews were conducted. Audio recordings were transcribed verbatim and entered into NVivo 10.0 (QSR International Pty Ltd, Doncaster, Victoria, Australia) for coding, analysis, and integration with demographic and asthma control data. Results were analyzed by the level of asthma control. A modified grounded theory approach was used in the analysis. Results: Thirty-five adults with persistent asthma (94% Black; 71% female; 71% with uncontrolled asthma) from the five West Philadelphia zip codes with the highest asthma burden participated. Generally, all participants understood the roles of inhaled corticosteroid (ICS) and short-acting β-2 agonist (SABA) therapies in asthma self-care although they attributed systemic side effects to topical ICS administration. Compared with participants with controlled asthma, uncontrolled participants reported overusing SABAs, underusing ICS, rejecting medical and trigger remediation advice, having more negative experiences with primary care providers, and preferring more unconventional strategies to prevent or manage asthma symptoms. Conclusions: Personal health beliefs about control can undermine adherence to medical and environmental remediation advice and likely contributes to high rates of uncontrolled asthma in this population. Clinicians need to know whether, and to what degree, these health beliefs can be modified. It is likely that new models of care, such as patient-centered shared decision-making approaches, and new partners, such as community health workers, may be required to modify these beliefs. This would be an important first step to enhance asthma control in vulnerable populations.